The Role of Family in Activity of Daily Living (ADL) Among Children With Intellectual Disability At State Special School Pembina Pekanbaru (Public Health Perspective Journal, 2018)
Activity of daily living (ADL) is a person's ability to perform activities independently. ADL is influenced by several factors, one of which is the role of family. The result of preliminary study at State Special School Pembina Pekanbaru showed that of,Â  6 children 10 children with intellectual disability aged 8-12 year had not been able to perform ADL as a whole. This study aims to determine the role of family and ADL and to analyze the role of family as a provider, the role of child care, the role of child socialization, family care of ADL for the children with intellectual disability at State Special School Pembina Pekanbaru. The study method was observational analytic with cross sectional design. The samples of this study were children with moderate level of intellectual disability aged 8-12 years as many as 43 children. The instrument used here was questionnaire. Data analysis used Chi Square test with significance level of 5%. The study results showed that there was a relationship between the role of family as provider and ADL (p-value 0,035). The role of family in child care and ADL (p-value 0,024). The role of family in child socialization and ADL (p-value 0,018). The role of family as nurse and ADL (p-value 0,024). This study is expected to provide input in developing programs that refer to government programs in dealing with children with intellectual disability so as to make a step of health promotion so that children with intellectual disability can know the importance of optimizing ADL needs independently.